Prosthodontic Management of Children with Hypohidrotic Ectodermal Dysplasia: Case Reports and a Review of the Literature - Maatouk, Fethi; Afia, Imene Ben; Masmoudi, Fatma; Laribi, Wafa; Ghedira, Hichem (The Journal of Dentists, 2015)
Hypohidrotic Ectodermal Dysplasia (HED) is a hereditary syndrome characterized by congenital defects in ectodermally derived structures as teeth, hair, skin and nails. Dental manifestations include abnormalities of form and number (hypodontia or anodontia) with subsequent aesthetic, psychological and functional consequences. Objectives: The purpose of this paper was to show through cases report that dental management help to improve the patient’s quality of life and to optimize their social integration. Methods: Two clinical cases about a boy and a girl, 8 and 6 years old respectively, with HED were exposed. They had a senile facial expression and presented a hypodontia with smooth dry skin, a hypotrichosis and an onychodystrophy. Management: After clinical and radiographic examination, a prosthetic rehabilitation was planned. Instructions on denture wear, hygiene and maintenance were given. Conclusion: In children with HED, an early oral management is essential because it gives a psychological boost and enhances conditions for normal growth and orofacial development. A close medical and psychological follow-up is needed.